Advances and perspectives in tooth tissue engineering. (6th May 2016) - Monteiro, Nelson; Yelick, Pamela C.
Abstract: Bio‐engineered teeth that can grow and remodel in a manner similar to that of natural teeth have the potential to serve as permanent replacements to the currently used prosthetic teeth, such as dental implants. A major challenge in designing functional bio‐engineered teeth is to mimic both the structural and anisotropic mechanical characteristics of the native tooth. Therefore, the field of dental and whole tooth regeneration has advanced towards the molecular and nanoscale design of bio‐active, biomimetic systems, using biomaterials, drug delivery systems and stem cells. The focus of this review is to discuss recent advances in tooth tissue engineering, using biomimetic scaffolds that provide proper architectural cues, exhibit the capacity to support dental stem cell proliferation and differentiation and sequester and release bio‐active agents, such as growth factors and nucleic acids, in a spatiotemporal controlled manner. Although many in vitro and in vivo studies on tooth regeneration appear promising, before tooth tissue engineering becomes a reality for humans, additional research is needed to perfect methods that use adult human dental stem cells, as opposed to embryonic dental stem cells, and to devise the means to generate bio‐engineered teeth of predetermined size and shape. Copyright © 2016 John Wiley & Sons, Ltd.